PHYTOCHEMICAL SCREENING AND ANTIDIABETIC ACTIVITY OF METHANOLIC EXTRACT OF CAYLUSEA ABYSSINICA LEAVES - Al-Kaf, Ali Gamal; Nelson, Nwali Onubuiwe; Patrick O, Ugwudike; Peace N, Amadi; Victor, Egbuji Jude; Okolie, Sandra Oluchi; Alexander, Idoko (Universal Journal of Pharmaceutical Research, 2023)
Introduction: Controlling type 2 diabetes with a treatment having no side effects remains a challenge for researchers even if the side effects are reduced and there may be a chance for reduced adverse reactions or severe side effects due to drug interaction. These interactions could result from concurrent use of dietary supplements or pharmacological therapy in addition to the medications. The current reading’s objective was to assess the qualitative and quantitative phytochemical analyses, and antidiabetic potentials of methanol leaf extract of Caylusea abyssinica (C. abyssinica) in diabetic rats. Methods: The qualitative and quantitative phytochemical analyses of total alkaloids phenol, and flavonoids were determined using the well-known test procedure outlined in the literature. The obtained C. abyssinica methanol leaf extract was used to examine in vitro anti-diabetic activity (α-Amylase inhibition), oral acute toxicity, and in vivo anti-diabetic activity against streptozotocin-induced diabetes rat model. Alkaloids, carbohydrates, reducing sugars, saponins, phenolic compounds, glycosides, tannins, and flavonoids were all established in the samples after phytochemical examination. Results: The amount of phenolics in the methanol leaf extract was (295.50 mg/g), with flavonoids coming in second (136.66 mg/g) and alkaloids coming in third (11.23 mg/g). The extract’s ability to inhibit α-amylase was investigated. The study’s findings show that the chosen plants had significant in vitro anti-diabetic effect. Up to 2000 mg/kg given over 14 days, the methanol extract’s acute toxicity trials did not reveal any harmful effects. Rats were given streptozotocin (60 mg/kg; i.p.) to induce diabetes, and glibenclamide (500 mcg/kg body weight) was utilized as the usual medication. Body weight, HDL, total protein, SGOT, SGPT, cholesterol, blood sugar levels, and triglycerides were all assessed in this study. Comparing diabetic rats to normal (control) rats, blood sugar and total protein, SGOT, SGPT, cholesterol levels, and triglyceride concentrations were all considerably (p< 0.001) reduced after oral administration of methanol extract of C. abyssinica at doses of 100 and 200 mg/kg and increased the level of HDL and body weight. Conclusion: As a result of the aforementioned findings, it can be said that C. abyssinica methanol leaf extract significantly reduces blood sugar levels in streptozotocin-induced diabetic rats. Peer Review History: Received: 5 October 2022; Revised: 9 November; Accepted: 17 December 2022, Available online: 15 January 2023 Academic Editor: Dr. Tamer Elhabibi , Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Reviewers: Dr. Sangeetha Arullappan, Universiti Tunku Abdul Rahman, Malaysia, sangeetha@utar.edu.my Prof. Hüsniye Kayalar, Ege University, Turkey, husniyekayalar@gmail.com